Regulasi Zakat di Indonesia; Upaya Menuju Pengelolaan Zakat Profesional - Muhammad Aziz; Sholikah Sholikah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2015)
In early Islamic history, described the involvement of government in managing it, with almost the same model, all of them can be said to be aimed at the welfare of the people. How does that happen in the context of the management of zakat in Indonesia with a Muslim majority, the actual management of zakat is good, people will be able to prosper. This paper wants to answer two questions, namely; how the history of the regulation of zakat in Indonesia? and secondly, why this charity regulation needs to be regulated in per-laws and regulations in Indonesia? This study used a qualitative approach to the study of comparative descriptive-analytical. The results of this study are that regulation is necessary charity regulated by the State, is in order to improve the effectiveness and efficiency of care in the management of zakat; and increasing the benefits of charity for the public welfare and poverty reduction. The effectiveness of the management of zakat in Indonesia pluralistic requires legal certainty and clarity of regulations that govern them